Lesbian and Gay Parenting - Taylor, Y. author. aut Link
XIII, 214 p.
Keywords: This book explores the intersections between class and sexuality in lesbians' and gay men's experiences of parenting and the everyday pathways navigated therein, from initial routes into parenting, to location preferences, schooling choice and community supports.